Cross-cultural translation and validation of the 'gut feelings' questionnaire into Spanish and Catalan. (2nd January 2019) - Oliva-Fanlo, Bernardino; March, Sebastià; Stolper, Erik; Esteva, Magdalena
Abstract: Background: The gut feelings questionnaire (GFQ) is the only tool developed to assess the presence of a 'sense of alarm' or a 'sense of reassurance' in the diagnostic process of general practitioners (GPs). It was created in Dutch and English and has validated versions in French, German and Polish. Objectives: To obtain a cross-cultural translation of the GFQ into Spanish and Catalan and to assess the structural properties of the translated versions. Methods: A six-step procedure including forward and backward translations, consensus, and cultural and linguistic validation was performed for both languages. Internal consistency, factor structure, and content validity were assessed. Results: Internal consistency was high for both questionnaires (Cronbach's alpha for GFQ-Spa = 0.94 and GFQ-Cat = 0.95). The principal component analysis identified one factor with the sense of alarm and the sense of reassurance as two opposites, explaining 76% of the total variance for the GFQ-Spa, and 77% for the GFQ-Cat. Conclusion: Spanish and Catalan versions of the GFQ were obtained. Both have been cross-culturally adapted and showed good structural properties.